2001
DOI: 10.1007/s00464-001-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

The umbilicus in laparoscopic surgery

Abstract: Wound infection at the umbilicus is similar to that at other sites, except after cholecystectomy. Postoperative ventral hernia at the umbilicus is similar to that at other sites and not related to preexisting fascial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
0
21
0
3
Order By: Relevance
“…In the Berlin quality study of 2007, the infection rate in 6539 patients was about 0.7%. However, others describe infections at the umbilicus after cholecystectomy in up to 9% of cases [42]. This discrepancy may be because many infections appear only after discharge from hospital and therefore do not appear in hospital statistics.…”
Section: Discussionmentioning
confidence: 89%
“…In the Berlin quality study of 2007, the infection rate in 6539 patients was about 0.7%. However, others describe infections at the umbilicus after cholecystectomy in up to 9% of cases [42]. This discrepancy may be because many infections appear only after discharge from hospital and therefore do not appear in hospital statistics.…”
Section: Discussionmentioning
confidence: 89%
“…15,16 However, Voitk et al and Hamzaoglu et al showed slightly higher rate of infections (9% and 8% respectively). 17,18 Kumar et al studied 104 patients and reported incidence of port site infection as 5.7%. 19 In present study port site bleeding was observed in 2% patients which is comparable to the reports of Quilici et al 20 Bleeding points can usually be identified and managed with electrocautery.…”
Section: Discussionmentioning
confidence: 99%
“…Dabei ist der umbilikale Zugang bei der laparoskopischen Cholezystektomie mit einer Infektrate von bis zu 9% mit Abstand am häufigsten betroffen [30]. In der von Voitk et al durchgeführten Studie [30] korrelierte die im Bereiche der Trokarstellen aufgetretene Wundinfektrate mit der Rate der postoperativ aufgetretenen Trokarhernien. So betrug die Trokarhernienrate bei stattgefundenem Wundinfekt 1,8%; bei fehlendem Wundinfekt jedoch nur 0,8% (p<0,05).…”
Section: Wundinfektunclassified
“…Bedenkt man, dass in der Regel pro laparoskopischem Eingriff 3 oder mehr Trokare verwendet werden, so kommt man zum Schluss, dass die Komplikation der Trokarhernie selten auftritt. Die meisten Autoren gehen von einer mittleren Inzidenzrate von 0,2-1,8% aus [15,17,18,20,30]. Im Vergleich dazu liegt die Rate der Narbenhernien nach offener Chirurgie eindeutig höher, nämlich bei durchschnittlichen 3-20% je nach Nachbeobachtungszeit.…”
Section: Introductionunclassified
See 1 more Smart Citation